FORMULASI DAN UJI AKTIVITAS GEL ANTIJERAWAT EKSTRAK UMBI BAKUNG (CRINUM ASIATICUM L.) TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS SECARA IN VITRO - Kumesan, Yuni Arista N; Yamlean,, Paulina V. Y.; Supriati, Hamidah S (PHARMACON, 2013)
Crinum asiaticum L. is a plant that has antibacterial activity toward Staphylococcus aureusbacteria, which is one of the pathogen bacteria that causing the acnes. This research purposed for made extract bulbs of Crinum asiaticum L. formula gel and tasted the physical characteristic toward Staphylococcus aureus. The formulation of extract bulbs of Crinum asiaticum L. is made with variety of extract concentration, which 1%, 5%, and 10% with CMC-Na as the basic. Negative control used basis gel and positive control used ErymedÂ® gel (Erytromicin 2%). Gel that is produced by physically tested covers: organoleptis, homogeneity, pH, dispersive power, and consistency. Antibacterial activity tested is done by diffusion method. Antibacterial activities data that are obtained by one way ANOVA with standard trust is 95%. The result of this research showed that extract bulbs of Crinum asiaticum L. had antibacterial activities with average resistibility zone diameter for 1% (8,3 mm) extract concentration, 5% (11,3 mm) extract concentration, 10% (16 mm) extract concentration, positive control (32 mm), and negative control (0 mm). Positive control counted as vey strong resistibility, extract concentration 5% and 10% counted as strong resistibility, extract concentration 1% counted as fair resistibility and negative control not given antibacterial activities. Key words: extract bulbs of Crinum asiaticum L., CMC-Na, antibacterial, Staphylococcus aureus.